Highly Multiplexed Digital Spatial Profiling of the Tumor Microenvironment of Head and Neck Squamous Cell Carcinoma Patients - Kulasinghe, Arutha; Taheri, Touraj; O’Byrne, Ken; Hughes, Brett G. M.; Kenny, Liz; Punyadeera, Chamindie (Frontiers in Oncology, 2021)
Background Immune checkpoint inhibitors (ICI) have shown durable and long-term benefits in a subset of head and neck squamous cell carcinoma (HNSCC) patients. To identify patient-responders from non-responders, biomarkers are needed which are predictive of outcome to ICI therapy. Cues in the tumour microenvironment (TME) have been informative in understanding the tumour-immune contexture. Methods In this preliminary study, the NanoString GemoMx™ Digital Spatial Profiling (DSP) technology was used to determine the immune marker and compartment specific measurements in a cohort of HNSCC tumours from patients receiving ICI therapy. Results Our data revealed that markers involved with immune cell infiltration (CD8 T-cells) were not predictive of outcome to ICI therapy. Rather, a number of immune cell types (CD4, CD68, CD45, CD44, CD66b) were found to correlate with progressive disease. Conclusion This study, to our knowledge, represents the first digital spatial analysis of HNSCC tumours. A larger cohort of HNSCC will be required to orthogonally validate the findings.